Maturation as a promoter of change in features of psychopathy between adolescence and emerging adulthood - McCuish, Evan C. (Youth violence and juvenile justice, 2022)
The relationship between psychopathy and negative behavioral, social, and health outcomes has lead to calls to identify factors that promote change in features of psychopathy. Given that maturation has important implications for changes in personality more broadly, it also may be informative of changes in specific personality traits associated with psychopathy. Rocque’s integrated maturation theory was used in the current study to guide the measurement of psychosocial, adult social role, and identity maturation domains among boys and girls from the Pathways to Desistance Study (n = 1,354). Based on cross-lagged dynamic panel models, within-individual change in temperance (psychosocial maturation), work orientation and consideration of others (adult social role maturation), and moral disengagement (identity maturation) predicted within-individual change in features of psychopathy measured using the Youth Psychopathic Traits Inventory. Maturation may influence features of psychopathy directly or indirectly through changes in a person’s social environment. Understanding why features of psychopathy change is an important step for developing person-oriented intervention strategies.